Keberlakuan dan Penerapan Undang-Undang Nomor 1 Tahun 2022 tentang Hukum Keuangan Pemerintah Pusat dan Pemerintahan Daerah sebagai Upaya Perwujudan Pemerataan Kesejahteraan Rakyat - Angelina, Noviyanti; Puji Simatupang, Dian (Alauddin Law Development Journal (ALDEV), 2023)
Since Law Number 1 of 2022 has existed in society, it has provided a number of implications including in the implementation of regional autonomy and decentralization. The scope of law reform which covers taxes and levies, management of transfers to the regions, management of regional expenditures, granting authority to carry out regional financing, and implementation of national fiscal policy synergies are considered as a step forward in carrying out reforms regarding central and regional financial relations. However, the enactment of this law is considered by several parties to be able to narrow the space for Regional Governments in implementing regional autonomy and decentralization. This article will see whether its existence has an impact and influence on the implementation of regional autonomy.